Dynamic vision from images to face recognition - Gong Shaogang; McKenna Stephen J; Psarrou Alexandra (London Imperial College Press, 2000)
This book describes the latest models and algorithms that are capable of performing face recognition in a dynamic setting. The key question is how to design computer vision and machine learning algorithms that can operate robustly and quickly under poorl
Keywords: Computer vision; Human face recognition (Computer science)